(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
This annotation analyzes the main properties of a parallelogram and a rhombus, the formulas for calculating their surface area, and their place in geometry. Properties such as parallel sides of a parallelogram, the division of diagonals into two equal parts, and the equality of all sides of a rhombus and the perpendicularity of its diagonals are covered on a scientific basis. The topic gives students a deeper understanding of geometric figures and improves their ability to apply theoretical knowledge in practical tasks.